Analysis of Effect the Greenhouse Gas Concetrations on the Air Temperature Rising in Pekanbaru City and Padang City - Aristya Ardhitama; Yusni Ikhwan Siregar; Nofrizal Nofrizal (Program Pascasarjana Universitas Riau, 2017)
Human activities have had an impact on global warming due to greenhouse gas emissions. Greenhouse gas emissions resulting from industrial activities, transportation and human activities that use fossil energy sources. The purpose of this research is to analyze the increase of air temperature using CO2 and CH4 gas concentration data from 2010-2016, to know the effect of greenhouse gases on the increase of air temperature, and to analyze the most influential factors in increasing air temperature in Pekanbaru and Padang City. The research method used is survey method with assessment and processing of secondary data. The research results found that greenhouse gases in particular the concentration of CO2 gas affect the temperature rise in Pekanbaru and Padang City. The increase of air temperature in Pekanbaru City is 0.52 °C up to 0.61 °C higher than the temperature rise in Padang City 0,51 °C up to 0.60 °C. The correlation of CO2 gas concentration with temperature rise in Pekanbaru City influenced the increase of air temperature by 10.2%. Factors that affect the most increase in air temperature in Pekanbaru City is the number of vehicles and the number of hotspots whereas in the city of Padang temperature rise is influenced by the number of vehicles and the number of industries. Government policies are required in mitigation efforts to reduce the impact of increased greenhouse gas concentrations by tree planting, peatland management and zero burning land clearing